NLRX1 does not play a role in diabetes nor the development of diabetic nephropathy induced by multiple low doses of streptozotocin - Scantlebery, Angelique M. L.; Uil, Melissa; Butter, Loes M.; Poelman, Renée; Claessen, Nike; Girardin, Stephen E.; Florquin, Sandrine; Roelofs, Joris J. T. H.; Leemans, Jaklien C. (PloS one, 2019)
Diabetic nephropathy (DN) is a microvascular complication of diabetes mellitus that results in both tubular and glomerular injury. Low-grade inflammation and oxidative stress are two mechanisms known to drive the progression of DN. Nucleotide-binding leucine-rich repeat containing family member X1 (NLRX1) is an innate immune receptor, uniquely located in mitochondria, that has been found to regulate inflammatory responses and to dampen renal oxidative stress by regulating oxidative phosphorylation. For this reason, we investigated the role of NLRX1 in the development of DN in a Type 1 Diabetes mouse model. We analyzed the effect of NLRX1 deficiency on diabetes development and the accompanied renal damage, inflammation, and fibrosis. We found that multiple low doses of streptozotocin induced body weight loss, polydipsia, hyperglycemia, glycosuria, and a mild DN phenotype in wildtype and NLRX1-deficient mice, without significant differences between these mouse strains. Despite increased NLRX1 expression in diabetic wildtype mice, NLRX1 deficiency did not affect the diabetic phenotype induced by streptozotocin treatment, as reflected by similar levels of polyuria, microalbuminuria, and increased renal markers of oxidative stress and inflammation in wildtype and NLRX1-deficient mice. The present findings show that NLRX1 does not mediate the development of streptozotocin-induced diabetes and diabetic-induced nephropathy in mice after multiple low doses of streptozotocin. This data implies that, while NLRX1 can be triggered by cellular stress, its regulatory and functional effects may be dependent on the specific physiological conditions. In the case of DN, NLRX1 may be neither helpful nor harmful, but rather a marker of metabolic stress.